Through-thickness work hardening variation in thick high strength steel plates - Denys, Kristof (Strojniški vestnik, 2024)
Due to the production process, thick high strength steel plates potentially exhibit inhomogeneous plastic material behavior through the thickness. For example, the initial yield stress and work hardening behavior might vary through the plate thickness. In order to establish a reliable plasticity model that can be used in finite element simulations to optimize forming processes or to investigate the structural integrity of large structures, this material behavior needs to be characterized. A straightforward characterization method consists of slicing the thick high strength steel plate and conducting standard tensile tests. However, this approach comes with a large experimental effort. A novel specimen is proposed enabling to inversely identify the work hardening behavior at distinct locations through the thickness of a thick steel plate. To this end, a tensile specimen with circular pockets at different depths is used. The strain fields within the pockets are captured using digital image correlation (DIC). finite element model updating (FEMU) is used to inversely identify a predefined strain hardening law for each pocket. First, the procedure is optimized and numerically verified using virtual experiments generated by a finite element model with a known variation of the work hardening behavior. Finally, the procedure is experimentally validated by characterizing the strain hardening behavior of a 10 mm thick S690QL grade.
Keywords: debelo jeklo visoke trdnosti; FEMU; Nelder-Mead; preoblikovalno utrjanje po globini; S690QL; stereo DIC; stereo-DIC; thick high strength steel; through thickness strain hardening